2013
DOI: 10.1128/jvi.02331-13
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequence Analysis of the Genome of RFHVMn, the Macaque Homolog of Kaposi's Sarcoma (KS)-Associated Herpesvirus, from a KS-Like Tumor of a Pig-Tailed Macaque

Abstract: eThe complete sequence of retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn), the pig-tailed macaque homolog of Kaposi's sarcoma-associated herpesvirus (KSHV), was determined by next-generation sequence analysis of a Kaposi's sarcoma (KS)-like macaque tumor. Colinearity of genes was observed with the KSHV genome, and the core herpesvirus genes had strong sequence homology to the corresponding KSHV genes. RFHVMn lacked homologs of open reading frame 11 (ORF11) and KSHV ORFs K5 and K6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Another primate rhadinovirus, retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn), carries a predicted miRNA precursor, miRc-RF9, with the potential to generate miRc-RF9-3p miRNAs with seed sequences identical to miRK10a and/or miR-K10a+1 ( Fig. 1A; Bruce et al 2013). To determine the 5 ′ -end(s) of miRc-RF9-3p, we cloned and expressed a 250-nt fragment of pri-miRc-RF9.…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another primate rhadinovirus, retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn), carries a predicted miRNA precursor, miRc-RF9, with the potential to generate miRc-RF9-3p miRNAs with seed sequences identical to miRK10a and/or miR-K10a+1 ( Fig. 1A; Bruce et al 2013). To determine the 5 ′ -end(s) of miRc-RF9-3p, we cloned and expressed a 250-nt fragment of pri-miRc-RF9.…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratesmentioning
confidence: 99%
“…Thus, Old World primate rhadinoviruses analyzed to date encode either miR-K10a or miR-K10a+1-like miRNAs. Other KSHV miRNAs have not been found to have counterparts in primate rhadinoviruses Bruce et al 2013), suggesting that miR-K10a/+1-like miRNAs may be particularly important components of the genetic makeup of Old World primate rhadinoviruses and KSHV.…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratesmentioning
confidence: 99%
“…In conclusion, the finding that KSHV and two other primate rhadinoviruses encode miRNAs bearing seeds of miR-K10a and/or miR-K10aϩ1 suggests that these miRNAs are important for rhadinovirus biology and pathogenesis (7,11,15,16). Alreadyidentified targets and functions of this miRNA include the repression of TWEAK and TGF-␤-induced effects on cell proliferation, apoptosis, and cytokine signaling (17,18).…”
Section: Discussionmentioning
confidence: 97%
“…However, the miR-K10a and/or miRK10aϩ1 seeds are the only KSHV miRNA seed sequences also found in miRNAs encoded by the related rhesus rhadinovirus (RRV) and retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn) (15,16). It therefore appears likely that miR-K10a/ϩ1 also have important seed-specific functions in rhadinovirus biology and pathogenesis, in addition to their sequence-independent role as regulators of Kap protein expression.…”
mentioning
confidence: 99%
“…The complete genome sequences have been determined for the pig-tailed macaque RV1 rhadinovirus RFHVMn (26), multiple variants of the rhesus macaque RV2 rhadinoviruses RRV17577 (27) and RRV26-95 (28), and the Japanese macaque RV2 rhadinovirus MfuRV2 (29). Comparison of genome sequences demonstrated that the RFHVMn and KSHV genomes were highly conserved.…”
mentioning
confidence: 99%